Evaluation of skeletal changes associated with surgically rapid palatal expansion without pterygomaxillary separation - BEYCAN, KADİR (ELSEVIER, 2020)
Introduction: To evaluate skeletal and nasal volume changes before and after surgery in surgically assisted rapid palatal expansion (SARPE) without pterygomaxillary separation and compare the dental changes by digital model analysis and radiographic analysis. Setting and sample: Population A total of 18 patients (10 females and 8 males) aged 15-33 years and with completed skeletal development, who were referred to Oral and Maxillofacial Surgery Department, Dentistry Faculty, Istanbul University and who had SARPE indication were included in the study. Materials and methods: Skeletal changes, lower nasal volume, transverse diameters of bony nasolacrimal duct and dental changes have been evaluated by using Cone beam computed tomography (CBCT) before and 6 months after the surgery. CBCT data was determined by Mimics v.18.01. Dental changes have been also evaluated by digital model analysis program 'Shape Orthoanalyzer' and the data are compared with those obtained using CBCT. Results: The results obtained from dental measurements made using CBCT and those obtained using scanning three-dimensional (3D) models were consistent with each other. CBCT demonstrated that lower anterior nasal volume and transverse diameters of bony nasolacrimal duct showed statistically significant increase before and after the surgery. Conclusions: According to the study findings, SARPE without pterygomaxillary separation was noted to be an effective procedure. Lower nasal volumes were increased and the maxilla expanded in the transverse direction in all patients. Dental evaluations that were performed in this digital model analysis also supported our findings in CBCT. Transverse diameters of the bony nasolacrimal duct were shortened at all patients. (C) 2019 Elsevier Masson SAS. All rights reserved.
Keywords: SARPE; Pterygomaxillary separation; Digital modals; Bony nasolacrimal duct; NASOLACRIMAL DUCT OBSTRUCTION; MAXILLARY EXPANSION; DOUBLE-BLIND; TOOTH-BORNE; DISJUNCTION; TERM; CBCT